What are the limits of accuracy in fetal weight estimation with conventional biometry in two-dimensional ultrasound?: a novel postpartum study - Kehl, Sven; Schmidt, Ulrich; Spaich, Saskia; Sütterlin, Marc (Ultrasound in obstetrics & gynecology, 2012)
Objective Commonly used formulae for fetal weight estimation, including combinations of several biometric parameters, lack accuracy despite efforts to improve them. This study aimed to investigate the limits of fetal weight estimation based on conventional biometric parameters on two-dimensional (2D) ultrasound by developing and evaluating new weight equations using postpartum biometric parameters. Methods This was a prospective multicenter study including 628 singleton pregnancies at term. Inclusion criteria were healthy newborns with no physical or chromosomal malformations. Postpartum measurement of head circumference, abdominal circumference and thigh length was performed. Six ‘best-fit’ formulae were derived using forward regression analysis in a formula-finding group (n = 419), and their accuracy was compared with birth weight in an evaluation group (n = 209) using percentage error, absolute percentage error, limits of agreement and the proportion of weight estimations falling within a discrepancy level of ± 10%. Results The new formulae showed no systematic error, with SD for the percentage error between 7.42 and 8.77 and no significant differences between median absolute percentage errors (4.84-5.71). They included 74.6-81.3% of neonates within a discrepancy level of 10%. With regard to the 95% limits of agreement, weight estimates were within a range of about ± 500 g. Conclusion These results show that a good sonographic weight formula has the following features: no systematic error, an SD of about 7% and inclusion of 80% of cases within a discrepancy level of 10%. The study indicates that the current accuracy of fetal weight estimation with conventional biometric parameters by 2D ultrasound has reached its limits. Further improvement will probably only be achieved through new approaches in ultrasonography. Copyright © 2012 ISUOG. Published by John Wiley & Sons, Ltd.
First published: 05 September 2011
Gesehen am 27.11.2018